The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1167/iovs.12-10621
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Properties and Correlation With Collagen Solubility Profile in the Posterior Sclera of Canine Eyes With anADAMTS10Mutation

Abstract: Citation: Palko JR, Iwabe S, Pan X, Agarwal G, Komáromy AM, Liu J. Biomechanical properties and correlation with collagen solubility profile in the posterior sclera of canine eyes with an ADAMTS10 mutation. Invest Ophthalmol Vis Sci. 2013;54:268554: -269554: . DOI:10.1167 PURPOSE. We examined the biomechanical properties and correlation with the collagen solubility profile of the posterior sclera in a canine model of primary open-angle glaucoma caused by the G661R missense mutation in the ADAMTS10 gene. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 49 publications
(51 reference statements)
4
37
0
Order By: Relevance
“…Like other ADAMTS, ADAMTS10 mutations may change biomechanical features of ECM in animals. 34 In our study, after insulin application, ADAMTS10 levels decreased in OUMS-27. Gruber et al 35 showed that ADAMTS10 was decreased in intervertebral disk degeneration.…”
Section: Discussionsupporting
confidence: 52%
“…Like other ADAMTS, ADAMTS10 mutations may change biomechanical features of ECM in animals. 34 In our study, after insulin application, ADAMTS10 levels decreased in OUMS-27. Gruber et al 35 showed that ADAMTS10 was decreased in intervertebral disk degeneration.…”
Section: Discussionsupporting
confidence: 52%
“…It may have a role in the storage and activation of latent transforming growth factor beta (TGF β ), which regulates the collagen turnover [41][43] as well as in the remodeling of the mesenchymal and basement membranes [44].…”
Section: Discussionmentioning
confidence: 99%
“…It maintains the lens in its position via lens ligaments, which are comprised primarily from fibrillin-1 [43]. Microfibrils localize and activate TGF β [45].…”
Section: Discussionmentioning
confidence: 99%
“…[65][66][67][68] Abnormalities in the ECM and the biomechanics of the optic nerve head's lamina cribrosa and the sclera also contribute to greater susceptibility of retinal ganglion cells to variations in IOP. [69][70][71][72][73][74][75] The recent discoveries of ADAMTS10 mutations responsible for POAG in beagles and Norwegian elkhounds, 25,76 as well as a mutation in ADAMTS17 causing canine PLL in many breeds, 29,77 and ongoing studies of canine POAG by the authors and others, 8,10 revealed that many forms of primary canine glaucoma are closely related to a group of connective tissue disorders resulting from abnormal microfibril formation. These so-called microfibrillopathies include Weill-Marchesani syndrome (WMS) and Marfan syndrome (MS) and are caused by mutations in genes responsible for normal microfibril formation, most importantly ADAMTS10, ADAMTS17, and fibrillin-1 (FBN1), resulting in defective microfibrils.…”
Section: Genetics Of Extracellular Matrix Abnormalities Associated Wimentioning
confidence: 99%
“…78,80,85,94,95 In support of the proposition that an abnormal ECM metabolism results from mutations in ADAMTS10, the authors observed that the sclera of mutant beagles is weaker and has biochemical differences compared with wild-type tissue. 75 They posit that the altered biomechanical properties of the ADAMTS10-mutant sclera has a neuroprotective effect and may partially explain their clinical observation that POAG-affected beagles maintain vision longer at high IOPs than PACG-affected dogs without an ADAMTS10 mutation.…”
Section: Genetics Of Primary Open-angle Glaucomamentioning
confidence: 99%